PERENCANAAN STRUKTUR PILAR (P1) JEMBATAN BETON BERTULANG SUNGAI PEPE KABUPATEN BOYOLALI, JAWA TENGAH - habibi abdush shodiq; Arief Rijaluddin (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2021)
The bridge is located in the Boyolali-Kartasura toll road construction project section 5, which was built to connect the semarang-solo toll road. This research was conducted with the aim of planning the under structure of the bridge using the reinforced concrete method, the bridge span is 84 meters with a bridge width of 12.5 meters. The structural planning only focuses on the pillar (P1) of the bridge. The calculation of bridge structure refers to RSNI T-12-2004 (Standard of Concrete Structure Planning for Bridge) and RSNI T-02-2005 (Bridge Planning Preparing Standard). The internal force calculation is calculated manually using structural analysis. Based on the analysis and calculations on the structure of the bridge, the results of the planning for pier head reinforcement use D32-100, for column reinforcement using D30-50, and for Foot Pier reinforcement using D32-100.